Clinical usefulness of patient-reported-outcome-measurement information system in Pediatric Crohn’s Disease: a cross-sectional study - Sara Azevedo; Maria Miguel Oliveira; Paulo Nogueira; Ana Isabel Lopes (Health and Quality of Life Outcomes)
Abstract Objectives This study evaluated the clinical utility of the Patient-Reported Outcomes Measurement Information System (PROMIS®) by comparing it with objective clinical data and validated health-related quality of life (HRQOL) measures in pediatric Crohn’s disease (CD) patients. Study design Cross-sectional study. Pediatric CD patients (aged 8–17 years) were enrolled prospectively over eight months from an outpatient pediatric gastroenterology center. We assessed the associations between PROMIS® Pediatric short-form measures, demographic and disease-related data, global clinical assessments, and HRQOL measures. A subanalysis according to the PCDAI (remission versus active disease) was also conducted. Results Thirty-one patients (mean age: 15.3; 58% female) with a mean disease duration of 2.7 years were included; 80.6% were in remission or had mild disease. The PROMIS® score was significantly correlated with several factors: age was negatively correlated with the PROMIS® Global Health Scale (r=-0.399; p = 0.026) and Life Satisfaction (r=-0.359; p = 0.047); sex was associated with the PROMIS® Cognitive Function Scale (t = 2.20; p = 0.038), favoring males; and school level was inversely related to the PROMIS® Peer Relationships (F = 3.90; p = 0.003). Clinical assessments also revealed significant correlations between hemoglobin and PROMIS® Global Health (r = 0.356; p = 0.049) and pain interference (r=-0.360; p = 0.046) and between ferritin and PROMIS® Meaning and Purpose (r = 0.435; p = 0.016) and cognitive function (r = 0.450; p = 0.011). Disease activity assessments correlated significantly with multiple PROMIS® measures, with better scores in patients in remission. Treatment changes, particularly corticosteroid treatment, negatively impacted the PROMIS® Anxiety and Life Satisfaction scores. IMPACT-III scores correlated positively with PROMIS® Global Health, Meaning and Purpose, Life Satisfaction, and peer relationships scores and negatively with Depression, Anxiety, Pain interference, and Fatigue scores. Group analysis indicated better PROMIS® scores and HRQOL scores in remission than in active disease remission. Conclusion Consistent with recent evidence, PROMIS® scores reliably reflect disease activity and HRQOL. The meaningful associations with clinical assessment and treatment efficacy reinforce the clinical relevance and utility of PROs in the patient-centered management of pediatric IBD and highlight the importance of self-reports as a gold standard tool for assessing health status.